1997
DOI: 10.1203/00006450-199703000-00011
|View full text |Cite
|
Sign up to set email alerts
|

Neuropsychologic Functions of Early Treated Patients with Phenylketonuria, on and off Diet: Results of a Cross-National and Cross-Sectional Study

Abstract: Twenty-two French patients with early treated phenylketonuria (PKU) off diet (no reduced phenylalanine, Phe) since their 5th birthday, 23 German patients on diet (reduced Phe), and 21 healthy control subjects from childhood to adulthood matched for age, sex, and IQ were investigated for visuomotor reaction time, sustained attention, and visual stimulus scanning. Determinations were made whether 1) the three groups showed different developmental trends in their reaction times, 2) the threshold of a Phe blood le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
52
1

Year Published

1999
1999
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(54 citation statements)
references
References 40 publications
1
52
1
Order By: Relevance
“…However, myelin deficiencies may explain reduced processing speed as well (Bick et al, 1991;Cleary et al, 1994;Koester, 1991;Rowland, 1991). Reduced vigilance and sustained attention, which have consistently been reported for PKU patients (Burgard et al, 1997;, may also result in slower (mean) processing speed. Reduced levels of noradrenaline (metabolites), which is associated with vigilance and sustained attention (Posner, 1993;Robbins & Everitt, 1994), have been found in the cerebrospinal fluid and autopsied brains of PKU patients (Krause et al, 1985;Lou, Lykkelund, Gerdes, Udesen, & Bruhn, 1987;McKean, 1972).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, myelin deficiencies may explain reduced processing speed as well (Bick et al, 1991;Cleary et al, 1994;Koester, 1991;Rowland, 1991). Reduced vigilance and sustained attention, which have consistently been reported for PKU patients (Burgard et al, 1997;, may also result in slower (mean) processing speed. Reduced levels of noradrenaline (metabolites), which is associated with vigilance and sustained attention (Posner, 1993;Robbins & Everitt, 1994), have been found in the cerebrospinal fluid and autopsied brains of PKU patients (Krause et al, 1985;Lou, Lykkelund, Gerdes, Udesen, & Bruhn, 1987;McKean, 1972).…”
Section: Discussionmentioning
confidence: 99%
“…Burgard et al, 1997). Impaired performance by PKU patients compared with control participants in the tracking and pursuit tasks showed deficiencies in motor control capacity.…”
Section: Discussionmentioning
confidence: 99%
“…Many reports have shown that optimum outcome occurs when dietary therapy is started early and continued indefinitely. 22,[25][26][27][28][29][30][31][32][33][34][35][36] As with other chronic illnesses, decreased compliance and poor dietary control increase with age, especially after 6 years of age. 17,25,37,38 Older individuals who have discontinued dietary therapy are at risk for developing loss of intelligence, magnetic resonance imaging findings consistent with white matter dysfunction, and occasionally acute demyelinating neuropathies.…”
Section: Of 9 Development Of Guidelines For Treatment Of Children Witmentioning
confidence: 99%
“…Discontinuation of dietary treatment bears a high risk of nutrient deficiencies, cognitive and emotional dysfunction as well as behavioral problems. Therefore, lifelong diet is strongly recommended (Stemerdink et al 2000;Burgard et al 1997;Weglage et al 1992).…”
Section: Introductionmentioning
confidence: 99%